Pengembangan Media Pembelajaran Pohon Geometri Untuk Meningkatkan Kosakata Pada Anak Tunarungu di SD - Kella, Christie; Rumampuk, Dhea; Harefa, Meiman; Dappa, Trihinas; Moningka, Angel; Sumilat, Juliana Margareta (Peneliti.net, 2023)
The problem experienced in learning by deaf students is the lack of vocabulary. Through this research aims to develop learning media in the form of Geometry Trees. This type of research is development research. By using a development research approach or RND with the Plomp model and development or Research and Development (R&D). The Plomp model used in the research has 2 stages of research, namely the preliminary stage and the formative evaluation stage which consists of self-evaluation, prototyping (expert reviews and one-to-one, and small groups), and field tests. This research was conducted with deaf students in grade 4 at SLB Paulus Tomohon for 4 months from July to October 2023. Data collection techniques were conducted by interview, observation, and test. Data analysis was carried out with the results of media, language, and material validators as well as the test results of deaf students. This Geometry Tree in addition to being a medium for increasing vocabulary, helps learning flat geometry to be fun. The results showed that the Geometry Tree teaching media helped increase vocabulary and recognize flat geometry shapes and their examples.